DENTAL AND ORAL HEALTH COUNSELING FOR ELEMENTARY SCHOOL STUDENTS IN NGGELA VILLAGE - Anderias Umbu Roga; Anggra Widianti (Jurnal Abdisci, 2024)
Children are still in a period of growth and development. Therefore, efforts to maintain oral health and dental health are critical, especially in the school and preschool environment. The development of dental health in adulthood is influenced by past dental conditions. Through counseling programs, communities can actively contribute to increasing their self-defense efforts and better understand the importance of maintaining their oral and dental health. This study aims to educate children about the importance of maintaining oral and dental health. Thus, children who receive counseling will better understand oral health.